Analisis Implementasi Kebijakan Just In Time Purchasing Pada Pengelolaan Bahan Baku Di CV. Inti Rotindo Group Pekanbaru - Andi Swerman Laia; Nur Fitriana; Rudi Syaf Putra (CV. ITTC INDONESIA, 2025)
This study aims to analyze the implementation of JIT purchasing policies in raw material management at CV. Inti Rotindo. This study uses a qualitative method with data collection techniques through interviews, observation, and documentation. The results of this study indicate that the implementation of JIT purchasing has not been fully implemented in accordance with the JIT purchasing concept. The company still purchases and stores raw materials in large quantities, resulting in storage costs that do not add value to the company. This is inconsistent with the JIT purchasing concept. Additionally, CV. Inti Rotindo has not yet established formal cooperation contracts with suppliers. As a result, suppliers do not deliver orders in small quantities.